Preparation and thermal degradation of 4-benzene sulfonylbenzyl methacrylate - Demirelli, K; Coskun, M; Dogru, M (Elsevier Sci Ltd, 2000)
The preparation and polymerisation of 4-benzenesulfonylbenzyl methacrylate are described. Thermal degradation of poly(4- benzenesulfonylbenzyl methacrylate) [poly(BSBzMA)] was studied by thermogravimetry (TG), FT-IR and NMR. Programmed heating was carried out at 10 degrees C/min(-1) from room temperature to 500 degrees C. Residual products of poly(BSBzMA) at various temperatures were examined by FT-IR spectroscopy. The cold ring fraction (CRF) of products volatile at degradation temperature but not at ambient temperatures has been characterized by GC-MS, FT-IR,C-13 and H-1 NMR techniques. The main products in thermal degradation of poly(BSBzMA) are 4-benzenesulfonylbenzyl methacrylate and 4-benzenesulfonyl toluene. The other liquid products of the degradation formation of anhydride ring structures and mechanism of degradation are discussed. (C) 2000 Published by Elsevier Science Ltd. All rights reserved.
Keywords: synthesis; sulfonylbenzyl methacrylate; thermal degradation